2007
DOI: 10.1111/j.1365-2516.2007.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of recombinant activated factor VII in southern Ontario in 85 patients with and without haemophilia

Abstract: Recombinant activated factor VII (rFVIIa) is licensed for the treatment of bleeding in individuals with haemophilia and inhibitors. The use of rFVIIa appears to be increasing, and an increase in unlicensed use is suspected. There are currently few data about the specific indications for its use. The aim of this study was to describe the patterns of utilization of rFVIIa. We performed a retrospective cohort study using rFVIIa infusion data collected prospectively and clinical data collected retrospectively. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Our study shows a consistent trend of increasing off‐label rFVIIa usage, both in the amount administered and in the number of patients receiving rFVIIa (Fig. 2) in keeping with previous retrospective studies (MacLaren et al , 2005; Ganguly et al , 2006; Webert et al , 2007; Heller et al , 2008; Isbister et al , 2008). The number of patients who receive it for on‐label indications remained relatively low, albeit the dosage amounts varied widely from 9·6 to 907·2 mg.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study shows a consistent trend of increasing off‐label rFVIIa usage, both in the amount administered and in the number of patients receiving rFVIIa (Fig. 2) in keeping with previous retrospective studies (MacLaren et al , 2005; Ganguly et al , 2006; Webert et al , 2007; Heller et al , 2008; Isbister et al , 2008). The number of patients who receive it for on‐label indications remained relatively low, albeit the dosage amounts varied widely from 9·6 to 907·2 mg.…”
Section: Discussionsupporting
confidence: 90%
“…Monitoring and reporting adverse drug reactions such as TAEs for rFVIIa is important for several reasons. First, its off-label utilization has rapidly increased and exceeds the number of patients receiving it for Ôon-labelÕ indications reported in several retrospective studies (MacLaren et al, 2005;Ganguly et al, 2006;Webert et al, 2007;Heller et al, 2008;Isbister et al, 2008). Second, its safety, including potential TAEs, has not been conclusively determined in nonhaemophilia populations even in randomized controlled trials (OÕConnell et al, 2006;Stanworth et al, 2007;Hsia et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have reported off-label use to similar degrees. 37,38,[45][46][47][48] We and others at our own institution recently completed a retrospective study of off-label rFVIIa usage patterns throughout the United States as part of a comparative effectiveness review for the Agency for Healthcare Research and Quality. 49 We found that, in 2008 (the most recent year of our analysis), 97% of inpatient uses of rFVIIa were off-label.…”
Section: Current Approaches To Guidelines For Use Of Rfviiamentioning
confidence: 99%